2019
DOI: 10.1007/s42452-019-0782-z
|View full text |Cite
|
Sign up to set email alerts
|

Removal of chemical oxygen demand from agro effluent by ZnO photocatalysis and photo-Fenton

Abstract: The direct discharge of improperly treated effluent from sago industry poses a great threat to water bodies due to the high amount of organic matter. This work investigated ZnO photocatalytic degradation under aerated and non-aerated conditions, and photo-Fenton aiming to reduce the chemical oxygen demand in sago effluent. Photolysis of sago effluent in the presence of ultraviolet irradiation and aeration resulted in 68% of the chemical oxygen demand removal. The results indicate high chemical oxygen demand re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is vividly shown that each of the nanoparticles has a rather low activity in the photodegradation of MB; however, a critical synergistic effect of those nanoparticles on each other enhanced the photocatalytic activity of the as-prepared nanocomposite and made it a promising choice for further studies. Additionally, the chemical oxygen demand (COD) method , was applied to investigate the quantitative degradation of MB as a pollutant. Based on the results (Figure S10), for the individual nanoparticles, Fe 3 O 4 and ZnO, the COD percentages are low, and in combination with the carbon-based nanomaterials, rGO and MWCNT, the COD percentages increased up to an unprecedented level over 90% for the rGO/MWCNT/Fe 3 O 4 /ZnO nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…It is vividly shown that each of the nanoparticles has a rather low activity in the photodegradation of MB; however, a critical synergistic effect of those nanoparticles on each other enhanced the photocatalytic activity of the as-prepared nanocomposite and made it a promising choice for further studies. Additionally, the chemical oxygen demand (COD) method , was applied to investigate the quantitative degradation of MB as a pollutant. Based on the results (Figure S10), for the individual nanoparticles, Fe 3 O 4 and ZnO, the COD percentages are low, and in combination with the carbon-based nanomaterials, rGO and MWCNT, the COD percentages increased up to an unprecedented level over 90% for the rGO/MWCNT/Fe 3 O 4 /ZnO nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, a chain reaction of free radicals was obtained in a cascaded form and these free radicals are bombarding on dye molecules and destruct them, and thereby, organic‐contaminants‐free water was obtained. [ 55 ]…”
Section: Resultsmentioning
confidence: 99%
“…In this way, a chain reaction of free radicals was obtained in a cascaded form and these free radicals are bombarding on dye molecules and destruct them, and thereby, organic-contaminants-free water was obtained. [55] 3.6. COD and BOD COD and BOD tests were analyzed for heterogeneous CTZ0-CTZ4 nanocomposites before and after the AOP, as shown in Tables 2 and 3.…”
Section: Advanced Oxidation Processmentioning
confidence: 99%
“…Pollution of the aquatic environment resulting from the discharging of insufficiently treated industrial wastes containing relatively large quantities of some chemicals of industrial origin, such as dyes, phenols, coloring materials, pesticides, and fertilizers, into water sources is a growing environmental problem and a direct threat to the life of all living organisms (1). In addition to being a major factor causing a lack of healthy food, disease, and death, water pollution often leads to a persistent shortage of clean drinking water accessible around the world (2).…”
Section: Introductionmentioning
confidence: 99%